Performance of UAV-Based Digital Orthophoto Generation for Emergency Response Applications - Akpinar, Burak (UIKTEN - ASSOC INFORMATION COMMUNICATION TECHNOLOGY EDUCATION & SCIENCE, 2021)
Unmanned Aerial Vehicles (UAVs) have been used for accurate orthophoto generation based on advanced Global Navigation Satellite System (GNSS) techniques. In recent years, the UAV systems have become an effective tool for fast monitoring of damages caused by disasters such as the earthquake hazards. The conventional orthophoto generation based on ground control points takes too much time during emergency situations. In the study, different methodologies for the processing of the acquired GNSS Positioning data for direct georeferencing of UAVs were investigated in terms of various orbit products. Evaluating the fitness for emergency response applications, the ground control points (GCPs) also used for validation of the generated orthophoto without using GCPs and based on Precise Point Positioning (PPP) approach. In this study, Ultra-Rapid, Rapid and Final PPP methods based on GNSS observations were used for direct geo-referencing. Thirteen GCPs were located at the study area for the validation of the orthophoto accuracy generated by direct geo-referencing.
Keywords: Unmanned Aerial Vehicles; Orthophoto; GNSS; Precise Point Positioning; Image Processing; AERIAL VEHICLE PHOTOGRAMMETRY; GPS; RECONSTRUCTION; ACCURACY; IMAGES; Computer Science